2016
DOI: 10.2340/16501977-2061
|View full text |Cite
|
Sign up to set email alerts
|

Self-rated health and return to work after first-time stroke

Abstract: Objective: Self-rated health is an essential aspect of life after stroke, and return to work is considered one of the most important outcomes for younger stroke patients. The aim of this study was to examine whether self-rated health 3 months after stroke, clinical and demographic determinants are independently associated with return to work and subsequent work-stability. Material and methods: A total of 590 patients with firsttime stroke were included from a Danish population-based cohort study. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 30 publications
0
35
1
Order By: Relevance
“…Even though the system of entering early retirement instead of sick leave after a long-term absence from work might reduce the RTW rate in Sweden, the system of giving wage subsides to employers for hiring persons with a disability could possibly contribute to a higher RTW rate. In the current study, the RTW rate at one year was 48.3%, compared with 75% in an Australian study [13], 50% in a Danish study [16], 62.4% in a Japanese study [29] and 35% in a study conducted in the UK [30]. Three different reviews with varying follow up time, mostly shorter than six years, additionally present substantially lower RTW rate than in the current study [3133].…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Even though the system of entering early retirement instead of sick leave after a long-term absence from work might reduce the RTW rate in Sweden, the system of giving wage subsides to employers for hiring persons with a disability could possibly contribute to a higher RTW rate. In the current study, the RTW rate at one year was 48.3%, compared with 75% in an Australian study [13], 50% in a Danish study [16], 62.4% in a Japanese study [29] and 35% in a study conducted in the UK [30]. Three different reviews with varying follow up time, mostly shorter than six years, additionally present substantially lower RTW rate than in the current study [3133].…”
Section: Discussioncontrasting
confidence: 57%
“…In the current study participants continued to RTW even up to three years post stroke, not shown previously with shorter follow-up time [13, 16]. The finding is important not only for patients but also for governments when creating policies regarding this major health and economic issue.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…6 Predictors for no RTW have been reported to be physical dependency at discharge, higher degree of residual disability, 11 sick leave prior to stroke, 9 unemployment prior to stroke, 12 low socio-economic status, 8 being an immigrant, 12 comorbidities, 12 older age 7 and being female. 6 Predictors for no RTW have been reported to be physical dependency at discharge, higher degree of residual disability, 11 sick leave prior to stroke, 9 unemployment prior to stroke, 12 low socio-economic status, 8 being an immigrant, 12 comorbidities, 12 older age 7 and being female.…”
mentioning
confidence: 99%